Coral Reef Bioerosion in the Eastern Tropical Pacific - Alvarado Barrientos, Juan José (2017)
Bioerosion, the weakening and erosion of hard substrates by boring, etching, and grazing organisms, is a major structuring force on coral reefs of the Eastern Tropical Pacific (ETP). Bioerosional processes are the main source of reef erosion, and facilitate recycling of reefal carbonate. In healthy reefs, a dynamic balance exists between destructive (i.e. bioerosion) and constructive (i.e. bioaccretion) processes, allowing for maintenance and growth of reef frameworks. In changing environments, however, bioerosion rates can exceed those of coral calcification, leading to reduced reef development and the destruction of reef frameworks. In the ETP, high rates of bioerosion are promoted by nutrient-rich upwelling and high primary productivity conditions, recurrent coral bleaching and mortality events, and a chemical environment characterized by high-pCO2 and low aragonite saturation state. Here we examine bioerosion in ETP coral habitats and the variable roles of reef-dwelling bioeroder taxa: microbial euendoliths (microendoliths), sponges, polychaetes, sipunculans, crustaceans, molluscs, echinoids, and reef fishes. Among these agents of bioerosion, sponges, sipunculans, bivalves, and echinoderms have been relatively well studied in this region, while information is currently lacking or limited for microendolith assemblages, polychaetes and reef fishes. The frequency of coral invasion by clionaid sponges (e.g., Cliona vermifera and Thoosa mismalolli) is variable between ETP coral habitats. Dense boring sponge assemblages can lead to high rates of carbonate losses exceeding those of bioaccretion. Boring bivalves (i.e., species of Lithophaga and Gastrochaena) are very abundant on many actively accreting reefs and are generally more prominent contributors to reef erosion in the ETP than in other regions. Sea urchins are by far the most destructive grazers of coral substrates in habitats where abundant. Following ENSO-associated coral mortality events, intense bioerosion by sea urchins has impeded coral recovery and compromised reef health at many eastern Pacific sites. This chapter reviews factors important in ETP bioerosion, and current knowledge of bioeroder populations in the region.